Effect of biofertilizers on early rooting, growth and nutrient status of Black Pepper - Ashithraj N (Department of Agronomy, College of Horticulture, 2001)
With an objective of studying the effect of vanous biofertilizers on establishment and growth of pepper cuttings, an experiment was conducted in the College of Horticulture, Vellanikkara during 1999-2000. Both lateral and runner cuttings were inoculated with five species of Glomus and three strains each of A.lipoferum and A.chroococcum. Observations were taken on germination and different growth parameters. Based on the early performance two species of Glomus and two strains each of A.chroococcum and Alipoferum were selected. Single, double and triple combinations of these selected microbes were studied further. Multiple inoculation was found to be supenor over single inoculations. Combinations involving AMF and nitrogen fixing bacteria were showing better results compared to two nitrogen fixing bacteria. Comparing the two species of AMF, Gfosciculatum was more effective in improving overall growth characters. Among nitrogen fixers, Alipoferum was more promising. Combination effect of Gfasciculatum and Alipoferum was appreciably good. However, addition of A.chroococcum with A.lipoforum and AMF further improved the growth performance of crop.